EFL Students’ Perceptions and Experiences on the Utilization of Ling App in Learning Pronunciation - Agustina, Titik; Hajimia, Hafiza; Yusran, Giofanny; Halawiyah, Izza; Farizi, Muh. Ikhlasul; Ariawan, Soni (FKIP Universitas Lampung, 2025)
EFL Students’ Perceptions and Experiences on the Utilization of Ling App in Learning Pronunciation. Objectives: This study investigates the use of the Ling app, an AI-driven tool, in learning pronunciation among EFL students in Islamic higher education. The research aimed to explore students' perceptions and experiences regarding the app's effectiveness in improving pronunciation skills. Methods: A mixed-methods approach was employed, combining quantitative data from questionnaires completed by 103 participants and qualitative data from interviews with 10 students. The questionnaire assessed perceptions of the app's usability and impact, while the interviews provided deeper insights into students' experiences and challenges. Findings: The findings indicate that the Ling app significantly enhances pronunciation proficiency, fosters learner confidence, and supports autonomous learning. Key features, such as speech recognition, real-time feedback, and gamified exercises, were particularly effective in enabling students to correct errors and practice independently. The app's interactive nature and gamification elements maintained student engagement and motivation. However, challenges were identified, including limited access to premium features, dependence on internet connectivity, and occasional inaccuracies in AI feedback when recognizing diverse accents. Despite these limitations, the app proved to be a valuable supplementary tool for pronunciation learning, offering flexible and engaging practice opportunities. The results underscore the app's potential to address significant gaps in traditional learning methods by providing self-paced and interactive learning experiences. Conclusion: The study concludes that the Ling app is a promising tool for EFL students, but further development is needed to enhance customization, address technical limitations, and cater to a wider range of learner needs, particularly in resource-constrained environments. Keywords: ling app, pronunciation, utilization.